Corporate Communication—Adversarial, Transmission, Dialogical. Issue 2 (3rd April 2019) - Tomaselli, Keyan; Caldwell, Marc
ABSTRACT: The trauma that followed organisational change through the twin inductions of transformation and New Public Management in some South African institutions of higher learning during the decade of the 2000s illustrates the need to pay attention to the communicative dimensions of organisational change. By means of a discussion of four kinds of workplace communication, this actual workplace study examines some specific instances of transformation and the restructuring of the South African tertiary sector, specifically, the hypothetical analytical composite New Name University (NNU) that represents an agglomeration of newly named and merged institutions that have become the visible form of the transformed edu-scape. The methodology was a lived one—action research—in that the authors were consulted by the university in which they were employed to analyse the prevailing corporate relations communication strategy and to suggest alternatives. The additional changes wrought by managerialism include new levels of bureaucracy alien to traditional academic culture and requirements of performance management that are no less onerous. The discussion suggests that a dialogical model of communication may well have brought about a different and more inclusive outcome than those that transpired in the NNU.